Proceedings of the 2011 Winter Simulation Conference (WSC) 2011
DOI: 10.1109/wsc.2011.6147983
|View full text |Cite
|
Sign up to set email alerts
|

Cross-paradigm simulation modeling: Challenges and successes

Abstract: This paper addresses the broad topic area of cross-paradigm simulation modeling with a focus on the discrete-event, system dynamics and agent-based paradigms. It incorporates contributions from four panel members with diverse perspectives and areas of expertise. First, each paradigm is described and definitions are presented. The difference between the process-oriented worldview and the event-oriented worldview within discrete-event simulation modeling, and the importance of this difference for crossparadigm m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 27 publications
0
35
0
2
Order By: Relevance
“…In 2011, Heath et al assembled a discussion panel representing a variety of perspectives on the topic of a hybrid method to use the simulation approaches ABS, SD and DES (Heath et al 2011). They concluded that, despite the progress made in simulation hybridization, a pragmatic modeling methodology and toolkit for developing complete hybrid models was still not well developed.…”
Section: Hybrid Methods: More Than Two Methodsmentioning
confidence: 99%
“…In 2011, Heath et al assembled a discussion panel representing a variety of perspectives on the topic of a hybrid method to use the simulation approaches ABS, SD and DES (Heath et al 2011). They concluded that, despite the progress made in simulation hybridization, a pragmatic modeling methodology and toolkit for developing complete hybrid models was still not well developed.…”
Section: Hybrid Methods: More Than Two Methodsmentioning
confidence: 99%
“…Los modelos de simulación discreta pueden desarrollarse a partir de tres enfoques (Heath, Brailsford, Buss y Macal, 2011;Pegden, 2010;Pidd, 2004):…”
Section: Simulación De Eventos Discretosunclassified
“…The idea to combine different simulation paradigms into a common environment helps to make complex simulation architectures easily handled and to profit from the advantages of different modeling approaches. Heath et al (2011) presented a discussion focused on cross-paradigm simulation modeling, using Discrete-Event Simulation (DES), System Dynamics (SD) and the Agent-Based (ABS) approach. Advantages and problems had been worked out considering pairs of different paradigms and software packages had been evaluated in light of hybrid simulation modeling.…”
Section: Related Workmentioning
confidence: 99%